RESEARCH ON THE CORRELATION BETWEEN SUBJECTIVE CONTROL AND THE INDEXES OF STUDY PROGRESS OF BACHELORS OF THE FACULTY OF PHYSICAL EDUCATION AND SPORT - Popovych, Ihor; Halian, Olena; Geiko, Ievgeniia; Zaverukha, Olha; Spytska, Liana; Bokhonkova, Yuliia; Fedyk, Oksana (Revista Inclusiones, 2020)
The purpose of the study is to examine the correlation between the psychological content parameters of subjective control and the indexes of study progress of the bachelors of the Faculty of physical education and sport It was established that there is no correlation between the psychological content parameters of subjective control (р<.05), and the knowledge quality in general education courses of the research students (р>.05). There is a quantitative and percent advantage of the indexes of the bachelors-teachers. We recommend implementing a flexible approach in organizing educational, training and competition processes of bachelors-sportsmen and applying combined variants taking into consideration the curricula, training schedules, maximum training loads and timetables of sportsmen’s participation in competitions. The obtained considerably lower indexes of internality in family relationships (M=33.12) and considerably higher indexes of internality concerning health and illness (M=18.22) of the bachelors-sportsmen are explained as subjective self-regulatory concentration of the bachelors-sportsmen on sport career and the aspiration for achieving sports results, in particular, individual or team achievements at the expense of psycho-physiological dominants, anthropological characteristics and health. The obtained results allow making local corrections to organizing and managing educational, training and competition processes at the stage of planning.